Характеристика цегли княжої доби у працях В. А. Богусевича - Махота, О.О. (Археологія і давня історія України, 2022)
Стаття присвячена внеску В. Богусевича у
вивчення цегли княжої доби з території Києва,
Чернігова, Путивля, Остра та інших міст. Проаналізовано його праці присвячені архітектурно-археологічним дослідженням пам’яток України
ХІ—ХІІІ ст. Виокремлено інформацію про параметри плінфи та деякі критерії, на які спирався
дослідник для визначення датування цегли княжої доби. Volodymyr Bogusevych researched various monuments
of archeology, art and architecture of the IX—
XVII centuries. He can be attributed to the constellation
of scholars who laid the necessary vectors for
studying the laws of architecture of the Princely Age.
The methods of architectural and archeological research
developed by V. Bogusevych still helps scholars
to study the monuments of stone architecture.
V. Bogusevych made a significant contribution to
the study of one of the main structural material of the
palace and temple architecture — the plinth. Having
started his academic path in this direction along
with the most famous experts in plinth (M. Karger,
P. Rappaport and M. Kholostenko), he developed his
own method of dating bricks of the Princely Age. However,
V. Bogusevych did not pay proper attention to
the coverage of the signs by which he dated the plinth.
Judging by the works of V. Bogusevych, most likely it
was its size. Also there is a tendency in his works to
date the bricks by presence of marks and end marks.
He collected a large collection of branded plinths from
Kyiv, Chernihiv, Ostra and Putivl and has repeatedly
participated in discussions about the possible purpose
of the signs.
Analyzing the works of V. Bogusevych, we can conclude
that he developed his terminological and conceptual
apparatus in the study of plinth gradually. It
was not until the 1950s that in his papers the word
«plinth» appeared next to the word «brick» to denote
this type of building material. This was influenced by
joint work with professional architects Yu. Aseev and
M. Kholostenko. After all, it is in joint work with them
that the use of these terms can be traced.
Of course, modern research methods have advanced
significantly in the study of plinths and sometimes refute
the conclusions of the scholar. But the source base
of brick sizes and signs on it significantly influenced
the development of modern methods of attribution of
plinths and is an extremely valuable source for future
generations of researchers of bricks of the Princely
Age.